Colombia's Negative Peace - a Challenge for Civil Society? - Goede, Wolfgang C. (2019)
Abstract: Colombia two and half years after the historic peace treaty with the FARC: The longest civil war in history has formally been pacified - but as yet, violence continues to rock the country. This dossier is about Colombia’s current status, what has been accomplished, and what remains to be done; about conflict lines and reconciliation strategies; about how peace researchers, journalists and human rights workers assess the situation; and about peace- making efforts of civil society in Colombia and Germany. I will argue that civil society has a unique role and potential in mediating conflicts, and in rendering peace-building processes more effective and in introducing innovative concepts to reframe academia and society